Spatiotemporal patterns and driving factors of NDVI changes in the central and Western Asia economic corridor over the past decade - Wang, Kaimin; Xu, Min; Wang, Shaohua; Wang, Lin; Tian, Haijing; Boonprong, Sornkitja; Gao, Xiaotong; Yang, Xinwei; Guo, Heyi; Li, Jingbo; Yang, Yujie; Hu, Ruichen; et al. (Frontiers in Environmental Science, 2025)
The Central and West Asia Economic Corridor (CWAEC) is a critical component of the Belt and Road Initiative (BRI), and that vegetation changes in the region are under significant uncertainty due to fragile ecological conditions, diverse climatic variability, and that these uncertainties are compounded by the interaction of natural factors and human activities. For the sustainable development of the CWAEC, it is urgent to pay attention to its regional environmental health. Using MOD13A3 NDVI data and ERA5 meteorological reanalysis data, this study evaluated the spatiotemporal changes in NDVI across the CWAEC over the past decade of BRI implementation. A trend analysis method was applied to assess NDVI development, and the relative impacts of climate change and human activities were explored through a multivariate regression residual analysis. The results revealed a declining trend in NDVI across the CWAEC, with an average rate of −0.26 × 10⁻2 a⁻1, and 50.74% of the region exhibiting insignificant degradation. Significant degradation was observed in the hilly areas of northern Kazakhstan, the low-altitude areas bordering the Tian Shan and Hindu Kush mountains, and the central part of the corridor. Conversely, significant restoration was concentrated in the hinterland of Kazakhstan and the coastal areas of the Caspian Sea. Climate change inhibited NDVI changes in 65.24% of the region, while human activities facilitated changes in 49.64%, indicating that the variations in NDVI were primarily driven by the combined effects of these factors. This study identifies the key drivers of NDVI changes in the CWAEC since the implementation of the BRI, provides scientific evidence to support the sustainable development of green BRI initiatives, and offers valuable insights for future ecological restoration and engineering projects within the corridor.